A monolithic, mortar‐based interface coupling and solution scheme for finite element simulations of lithium‐ion cells. (25th March 2018) - Fang, Rui; Farah, Philipp; Popp, Alexander; Wall, Wolfgang A.
Summary: This work introduces a novel, mortar‐based coupling scheme for electrode‐electrolyte interfaces in 3‐dimensional finite element models for lithium‐ion cells and similar electrochemical systems. The coupling scheme incorporates the widely applied Butler‐Volmer charge transfer kinetics, but conceptually also works for other interface equations. Unlike conventional approaches, the coupling scheme allows flexible mesh generation for the electrode and electrolyte phases with nonmatching meshes at electrode‐electrolyte interfaces. As a result, the desired spatial mesh resolution in each phase and the resulting computational effort can be easily controlled, leading to improved efficiency. All governing equations are solved in a monolithic fashion as a holistic, unified system of linear equations for computational robustness and performance reasons. Consistency and optimal convergence behavior of the coupling scheme are demonstrated in elementary numerical tests, and the discharge of two different realistic lithium‐ion cells, each consisting of an anode, a cathode, and an electrolyte, is also simulated. One of the two cells involves about 1.35 million degrees of freedom and very complex microstructural geometries obtained from X‐ray tomography data. For validation purposes, characteristic numerical results from the literature are reproduced, and the coupling scheme is shown to require considerably fewer degrees of freedom than a standard discretization with matching interface meshes to achieve a similar level of accuracy.